Liver and spleen elastography in diagnosis of extrahepatic portal vein obstruction: pilot study - M. Yu. Nadinskaya; Ye. O. Liusina; Ch. S. Pavlov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate diagnostic value of liver and spleen elastography in patients with extrahepatic portal vein obstruction - non-cirrhotic portal vein thrombosis (PVT). Material and methods. The study group: 19 patients (Age 21-76 years) with PVT diagnosed by multispiral computed angiography without liver/pancreatobiliary tumors and/or liver cirrhosis (LC). The comparison group included 23 patients with LC Child-Pugh class A. Past history of portal hypertension, platelet count, serum albumin level, alanine and aspartate aminotransferase level; prothrombin according to international normalization ratio; grade of esophageal varices (EV); spleen longitudinal size according to abdominal ultrasound, liver and spleen stiffness were evaluated in both groups. Results. The group of patients with non-cirrhotic PVT was characterized by presence of clinically significant portal hypertension (EV, splenomegaly and hypersplenism). Following causes for PVT were established: systemic factors - myeloproliferative diseases, G20210A prothrombin gene mutation, and local factors: complications after pancreatobiliary surgery, omphalitis and neonatal umbilical sepsis. Nine patients, 1 to 2 years prior to hospitalization, were previously misclassified as «cryptogenic liver cirrhosis» in various medical institutions. Liver stiffness in PVT group was 2,8-11,5 kPa. The grade of EV tended to increase along with progression of the spleen stiffness. Statistically significant difference in serum aminotransferases levels in non-cirrhotic PVT vs Child-Pugh class A HCV-LC was observed: enzyme levels were 1,5-2 fold higher in LC (р